Effect of Slow Breathing Exercise on some cardio vascular functions in Type 2 Diabetic Male Patients - Yesmin, Jenefer; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2021)
Background: Slow breathing exercise (SBE) has some useful effects on cardiovascular system. Objectives: To observe the effects of slow breathing exercise on blood pressure in male patients with type 2 diabetes mellitus (DM). Methods: This interventional study was implemented on sixty (60) diagnosed male type 2 diabetes mellitus (T2DM) patients aged 45-55 years with disease history 5-10 years, selected from Out Patients Department (OPD) of Endocrinology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. The subjects were divided into two groups, control group (n=30) included type 2 DM patients without SBE and study group included patients performing SBE for 3 months(n=30) and they were enrolled bypurposive sampling method. The study group was advised to practice SBE for 30 minutes 2 times daily for 3 months. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure(MAP),pulse pressure(PP) and rate pressure product (RPP)were recorded at the start of the study and after 3 months in both group of patients.. Independent sample t test and paired sample t-test were used for statistical analysis and p<0.05 was taken as statistical significance. Results: In this study, the value of mean HR, SBP, DBP, MAP and RPP were significantly (p<0.05) reduced after 3 months of SBE. Again no significant changes observed (p>0.05) after 3 months in the group who did not practice SBE. Conclusion: Cardiovascular functions in T2DM patients was improved after performing slow breathing exercise for 3 months. J Bngladesh Soc Physiol 2021;16(1): 11-15